Kajian Feminisme dalam Novel “Cantik Itu Luka” Karya Eka Kurniawan - Katharina Woli Namang; Yeremias Bardi; Nur Sakinah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Feminism studies are studies that focus on the movement of women to gain freedom and determine themselves. In this beautiful novel Luka depicts the oppression of women during the Japanese colonial period. The beautiful novel Luka shows the resilience of a mixed Dutch and native woman who was detained by the Japanese army and had to be forced to work as a prostitute. The problem of this research is what is the psychological aspect of feminism analysis contained in the beautiful novel Luka by Eka Kurniawan? What is the social aspect of feminism analysis? contained in the novel